ANALISIS PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA FISIK TERHADAP LOYALITAS KERJA KARYAWAN MELALUI KEPUASAN KERJA KARYAWAN SEBAGAI VARIABEL INTERVENING (Studi pada Kantor Direksi PT Perkebunan Nusantara IX Divisi Tanaman Tahunan) - Ramadhani, Zahrah Putri; Rahardjo, Mudji (Diponegoro Journal of Management, 2017)
There is a research gap in previous studies between the influence of compensation on job satisfaction and employee loyalty, and the influence between the physical work environment on job satisfaction and employee loyalty. So that research aims to determine the influence of compensation and physichal work environment towards employee loyalty that mediated by job satisfaction at Office Directors of PT Perkebunan Nusantara IX Divisi Tanaman Tahunan Semarang.The sampling method used on this research is proportional random sampling. Data was collected through questionnares to 60 respondents who are employees at Office Directors of PT Perkebunan Nusantara IX Divisi Tanaman Tahunan Semarang. The techniques of data analysis in this research includes the test of validiy, reliability, classical assumptions test, path analysis, Sobel test to examine the mediation effect, and hypothesis test.The results of analysis and discussion indicates that compensation and job satisfaction had positive and significant effect on employee loyalty. While physical work environment has no significant effect on employee loyalty. Furthermore, job satisfaction is proven as mediator relathionship between compensation and physical work environment on employee loyalty.